Malawi Economic Monitor, December 2019 : Strengthening Human Capital Through Nutrition - World Bank (World Bank, Lilongwe, Malawi, 2019)
With Malawi’s economic growth recovering and single digit inflation, the Government has a keyopportunity to rein in fiscal deficits and reduce domestic debt. If it can better control domestic debt levels, the Government could increasingly move towards creating the conditions for the privatesector to increase investment, which can drive growth and job creation. To support this, the Government needs to develop a track record of achieving sustainable fiscal deficits in order to contain and reverse the escalating domestic debt burden, to contain interest rates and avoidcrowding out private sector investment, and to increase public investment. Malawi’s economy is projected to grow by 4.4 percent in 2019, up from 3.5 percent in 2018. Agricultural activity rebounded in 2019 due to favorable weather conditions, which offset the negative effects from Tropical Cyclone Idai in parts of the southern region of the country. Crop production was generally strong, particularly in the case of maize, with production increasing by 25.7 percent. This supported overall economic growth, despite a decline in tobacco production. However, the ongoing political impasse, with widescale demonstrations that have continued since May 2019, has constrained business activity and increased uncertainty, weighing on investment. The Government missed the revised fiscal deficit target in FY2018/19. The fiscal deficit increased to 6.5 percent of GDP, higher than the revised target of 5.8 percent. The impact of election-related expenses,increased interest payments and costs associated with the disaster response pushed recurrentexpenditure beyond targeted levels by 1 percent of GDP. This was partially offset by under-execution of development expenditure, which was not enough to keep the fiscal deficit to 5.8 percent of GDP. Poor revenue performance, which was lower by 0.5 percent of GDP, compounded the problem.